Regulation of the Unfolded Protein Response in Yeast by Oxidative Stress - Guerra-Moreno, Angel (FEBS Lett, 2019)
In the unfolded protein response (UPR), Ire1 activates Hac1 to coordinate the transcription of hundreds of genes to mitigate ER stress. Recent work in C. elegans suggests that oxidative stress inhibits this canonical Ire1 signaling pathway, activating instead an anti-oxidant stress response. We sought to determine whether this novel mode of UPR function also existed in yeast, where Ire1 has been best characterized. We show that the yeast UPR is also subject to inhibition by oxidative stress. Inhibition is mediated by a single evolutionarily conserved cysteine, and affects both luminal and membrane pathways of Ire1 activation. In yeast, Ire1 appears dispensable for resistance to oxidative stress and, therefore, the physiologic significance of this pathway remains to be demonstrated.